SFA-based learning material design to improve English medical terminology acquisition among South East Asian nursing students - Diannike Putri; Barlian Kristanto; Tri Sumarni; Thanee Glomjai; Gary Garay; Dung Le Hoang (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2023)
The study explicates the utility of Semantic Feature Analysis (SFA) in developing educational resources with the intent to facilitate the acquisition of medical English terminology among nursing students. This study employs a Research and Development (R&D) methodology to devise and evaluate the efficacy of pedagogical resources centered on the Systematic Functional Approach (SFA). The purpose of the present study is to conduct a comprehensive literature review to examine the importance of medical English terminology for nursing students, as well as the role of Speech Familiarity Aid (SFA) in designing educational materials. Furthermore, this review seeks to investigate contemporary research findings concerning the effectiveness of SFA in facilitating language acquisition. The research findings reveal that learning materials based on SFA substantially enhance the acquisition of medical English terminology among nursing students, underscoring the prospect of SFA as an efficient means for the development of language learning resources.